ANALISIS KESEJAHTERAAN PETANI NIRA KOPERASI SEMI RAHAYU MANDIRI UNTUK MENGEMBANGKAN PEREKONOMIAN LOKAL - Ruslina Baeti; Mutia Pamikatsih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the level of welfare of sap farmers in the Semi Rahayu Mandiri Cooperative and to determine the effect of the farmer's age, number of trees, length of work and land ownership on the amount of production produced by the farmers collectively. This research was conducted in the semi-rahayu independent cooperative with a sample of 30 sap farmers who are members of the cooperative. This study uses interview and observation methods, a type of quantitative research using descriptive statistical analysis. The results of this study show that the sap farmers who are members of the Semi Rahayu Mandiri Cooperative are said to be prosperous with an average income value of IDR 4,391,167 per month, this income is above the poverty line or poverty line in Cilacap Regency. With the level of welfare owned by farmers so that they can improve their quality of life, based on the total income earned by farmers, they have the potential to develop the local economy so that it becomes a leading sector. Therefore farmers work together in cooperatives to improve their institutions with the aim of stabilizing the selling price of coconut sugar.